Outcomes in thread lift for face and neck: A study performed with Silhouette Soft and Promo Happy Lift double needle, innovative and classic techniques. (13th August 2018) - Rezaee Khiabanloo, Samad; Jebreili, Roghieh; Aalipour, Ezatollah; Saljoughi, Nazi; Shahidi, Arian
Abstract: Introduction: Increased demand for rejuvenation of the aging face has led to the evolution of various plastic surgery techniques. This study was conducted to evaluate the surgical efficacy and outcomes of the absorbable suture suspension system related to eyebrow, midface, mandibular, and neck lifting. Materials and Methods: In this prospective review chart clinical study, a total of 193 patients were included in the study from January 2016 to May 2017. All participants underwent thread lifting using the Proma Happy Lift double needle and Silhouette Soft threads. The patients were followed up for first week and first, third, and sixth month after lifting surgery. Outcomes were assessed by two surgeons and patients based on the GAIS score. Results: A total of 193 patients (mean age: 52.22 ± 11.74 year, range: 25‐89), 23 (11.9%) men and 170 (88.1%) women, were included in the study. The most common sites for the face lifting surgery were the jawline (46.1%), midface (33.7%), eyebrows (12.4%), and neck (7.8%). The level of satisfaction increased from 94% in the first week after surgery to 99% in the sixth month after surgery for patients, increased from 94% to 99% for surgeon 1, and increased from 83% to 98% for surgeon 2. Conclusion: The results showed that the level of satisfaction of patients and surgeons increased over time. These results demonstrated that facial rejuvenation thread lift with Proma Happy Lift double needle and Silhouette Soft threads is a being cosmetically more acceptance, safe, and effective procedure associated with minor complications.